2011
DOI: 10.1128/aem.02740-10
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Gene Expression on Demand: an Inducible, Tunable, and Metabolism-Independent Expression System for Aspergillus niger

Abstract: Filamentous fungi are the cause of serious human and plant diseases but are also exploited in biotechnology as production platforms. Comparative genomics has documented their genetic diversity, and functional genomics and systems biology approaches are under way to understand the functions and interaction of fungal genes and proteins. In these approaches, gene functions are usually inferred from deletion or overexpression mutants. However, studies at these extreme points give only limited information. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(174 citation statements)
references
References 45 publications
3
167
0
4
Order By: Relevance
“…To further confirm that the metH gene is indispensable for A. fumigatus, we constructed a conditional expression strain, AfS180, in which the expression of the coding sequence is driven by a doxycycline-dependent Tet-ON module (see Fig. S7 in the supplemental material) (74,75), a system that has successfully been used in A. fumigatus to prove gene essentiality (76). In the presence of doxycycline, the metH gene is properly expressed to support growth of AfS180 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm that the metH gene is indispensable for A. fumigatus, we constructed a conditional expression strain, AfS180, in which the expression of the coding sequence is driven by a doxycycline-dependent Tet-ON module (see Fig. S7 in the supplemental material) (74,75), a system that has successfully been used in A. fumigatus to prove gene essentiality (76). In the presence of doxycycline, the metH gene is properly expressed to support growth of AfS180 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…pCH003 was constructed by cloning rho1 (PCR amplified with primers Rho1-6g06900fufnew and Rho1-6g06900-rev with chromosomal template DNA) in pJW121. pJW121 was constructed by cloning the tetracycline-dependent transactivator, the crgA terminator, and the tetO7::Pmin (a blunt-ended fragment derived from pVG2.2 after digestion with EcoRI and PmeI [22]) into the PmeI site of pSK379. pJW103 and pSK379 were described previously (7,23).…”
Section: G14vtetonmentioning
confidence: 99%
“…7f). Note that it is unlikely that Tet-On mediated expression is insufficient to induce overexpression of the endogenous ssoA, as it was previously shown that the Tet-On system enables expression levels similar to gpdA expression (Meyer et al, 2011a), which in fact would be 80-fold higher than ssoA expression (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…Mutant alleles of ssoA (encoding SsoA L81F , SsoA L81G , SsoA R212K and SsoA R212P ) were generated by PCR using primers carrying the respective mutations and XhoI-EcoRI ends. The For the creation of a conditional ssoA overexpression construct using the Tet-On system, the ssoA ORF or ssoA ORF with a truncated transmembrane domain (ssoADTM) was cloned into pVG2.2 (Meyer et al, 2011a) and the resulting plasmid was transformed for targeted integration at the pyrG locus using the pyrG* marker. After Southern blot analysis, strains were selected (MK22.3 and MK24.20) that contained the wild-type ssoA gene or ssoADTM gene at the pyrG locus under control of the tetracycline promoter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation